Non- obviousness of biography as a research subject of a pedagogue - Magda Karkowska (Studia z Teorii Wychowania)
The aim I set for myself is to reveal what connects the main areas of biography research - literary and social - and to show what importance for upbringing, as well as for biographical research carried out in the field of pedagogy, are attempts to combine them. Problem and research methods: The main problem was formulated as the question: What makes a biography non-obvious? Another problems: What analytical categories relating to biography best capture this non-obviousness? What is the specificity of studying biography by educators and how do such analyzes differ from sociological or literary studies? The main method is to analyze the concepts that make up the research field and the relationships between them. In the first part of the article, I outline the relationship between biography and the construction of narrative identity, in order to show the way of understanding key concepts, such as narrative or story, as they constitute a specific basis for an attempt to grasp the meanings and dimensions of the title non-obviousness of a biography. Then I analyze the phenomena essential for the construction of identity: secrets, existential crises, trajectories or epiphanies. The next step is the analysis of categories such as the internal structure of life, as well as the image of life, ready biography, biography in interaction and autonomous biography. In the second part of the article, based on the concept of biography by Duccio Demetrio, I consider the specificity of pedagogical studies on the phenomenon of biography. The article concludes with conclusions on the specificity of pedagogical research on biographies and their relationship with therapeutic activities. As a result of the analysis, I come to the conclusion that the non-obviousness of the biography comes from the individual way of experiencing it. It is a set of features, a result of specific events, choices made, and at the same time a consequence of answering important existential questions. The aforementioned phenomena that are crucial for the construction of identity-occurrences are of particular use in its analysis. The pedagogical study of biography is different from sociological or literary analyzes, it turns out to be work with the collected biographical materials as well as with another human being and has, apart from cognitive values, a therapeutic dimension